FAM46C as a Potential Marker for Pan-Cancer Prognosis and Predicting Immunotherapeutic Efficacy - Deng, Jiehua; Xiao, Wei; Wang, Zheng (Frontiers in Genetics, 2022)
BACKGROUND: FAM46C is a common mutated gene in tumours. A comprehensive understanding of the relationship between FAM46C expression and pan-cancer can guide clinical prognosis and broaden the immunotherapeutic targets. METHODS: Data from The Cancer Genome Atlas (TCGA) and Genotype-Tissue Expression (GTEx) databases were obtained, and gene expression of different tumour types and stages was analysed. Immunohistochemical analysis was performed to detect differences in the FAM46C protein levels in normal and cancerous tissues. The genetic variation of FAM46C was characterised using cBioPortal. The clinical prognostic value of FAM46C and the impact of FAM46C expression levels on the prognosis of patients with different types of cancer were assessed based on Kaplan–Meier and Cox regression analyses. Gene set enrichment analysis (GSEA) was used to analyse the pathways associated with FAM46C. Correlations between FAM46C expression levels and immune infiltration were assessed using the TIMER2 database and CIBERSORT algorithm, and correlations between FAM46C expression and the ESTIMATE, immune and stromal scores were analysed using the ESTIMATE algorithm. In addition, we also analysed the correlation between FAM46C expression and immune activation, suppression genes and immune chemokines. RESULTS: The expression level of FAM46C was correlated with the prognosis of most tumours, and low expression levels often suggested a poor prognosis. FAM46C was positively correlated with the abundance of CD4+ T cells, CD8+ T cells and plasma B lymphocytes in the tumour microenvironment. FAM46C exhibited a strong correlation with immunomodulatory pathways, immunomodulatory factors and immune markers. In addition, high FAM46C expression correlated with tumour mutational burden(TMB) in acute myeloid leukaemia and microsatellite instability(MSI) in endometrial cancer. CONCLUSION: Our study suggests that FAM46C can be a potential prognostic marker for pan-cancer, is closely associated with immune regulation and may be an immune checkpoint to guide future clinical immunotherapy.